Investigation on the behaviors of Tou–Kung sets in historic timber structures. Issue 3 (February 2020) - Xue, Jianyang; Ma, Linlin; Dong, Xiaoyang; Zhang, Xin; Zhang, Xicheng
To investigate the structural performance of Tou–Kung, two 1/3.52-scaled models of Tou–Kung were designed and tested subjected to vertical loading and quasi-static loading. Also, the finite element models of intact Tou–Kung and tilting Tou–Kung were established. Based on the validation of experimental results and finite element models, numerical simulation analysis of the models was carried out to study the influence of tilting angle on the behaviors of Tou–Kung. It is shown that the failure modes of the models were the compressive fracture of Da-Tou under vertical load, the shear failure of the dowel at Da-Tou, and the slipping between Da-Tou and Pingban-Fang subjected to lateral cyclic loads. The relationship of vertical load and vertical displacement was obtained and analyzed, and the vertical initial stiffness and bearing capacity of the models descended with the increase in tilting angle. The hysteretic loops of the tilting models subjected to cyclic loads are asymmetrical in positive and negative loading, and the asymmetrical degrees of the curves are much significant with a larger tilting angle of the models. With the increase in tilting angle, the lateral stiffness and ultimate load increased in positive loading, and both of them decreased in negative loading due to the tilting of the models. Also, the equivalent viscous damping coefficient of the models decreases with a larger tilting angle of Tou–Kung.